Oral History Interview with Amanda Mondlock by Lois Helland - Helland, Lois; Mondlock, Amanda (My University, 2009)
This interview is part of an oral history project conducted in honor of 25th anniversary of the Women's Studies Program at the University of Wisconsin - Eau Claire.